Corporate risk management and firm performance: Sri Lankan perspective - Rozairo, H.P.; Samarakoon, S.M.R.K. (University of Jaffna, 2020)
Risk management and firm performance in organizations became crucial when it involves research over a previous couple of decades and remains widely discussed globally. The tendency is to take a holistic overview of risk management instead of considering risk management from a silo-based view. This holistic approach to risk management is usually mentioned as Corporate Risk Management (CRM). There are so many shreds of evidence for the statement that organizations will enhance their performance by using the CRM concept. The main objective instigated during this study is that the proper match between corporate risk management (CRM) and, therefore, the firm factors: namely, Industry competition (CI), firm size (FS), firm complexity (FC), and monitoring by the board of directors (MBD) and the relationship among CRM and firm performance (P). Supported a sampling of 60 firms in CSE, reflecting the maintaining of their CRM operations in their annual reports, empirical evidence supports the main argument instigated above. These findings mean that firms should implement the CRM in aggregation with the appropriate variables adjoining the firm.
Keywords: contingency theory; corporate risk management index; firm performance; Sri Lanka